"Mythos" and "Logos": "poetic-epistemic authority" in Early Greek philosophy - Di Iulio, Erminia (Rivista Italiana di Filosofia del Linguaggio, 2022)
This paper focuses on the transition in ancient Greek thought from mythos (understood as “narration”) to logos (understood as “argumentation”). The aim is to investigate the difference between “mythos/narration” and “logos/argumentation” assuming the point of view of their respective conception of “(epistemic) authority” and “epistemology of testimony”. My basic claim is that Parmenides’s Poem is the turning-point in which “narration/mythos” gives way to “argumentation/logos” and that this becomes clear if we take a closer look at Parmenides’s own relationship to Hesiod. In order to develop my argument, I shall put both Parmenides’s and Hesiod’s claims within the framework of contemporary epistemology of testimony, for it might shed new light on these issues.